2006
DOI: 10.1111/j.1556-4029.2006.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Accidental Intrathecal Injection of Vindesine

Abstract: A 25-year-old woman being treated for non-Hodgkin's lymphoma was accidentally given vindesine intrathecally. The error was recognized immediately and a spinal cord washing was performed through syringing with isotonic saline. However, the patient died 6 weeks later with increasing paralysis, which was followed by neurologic failure. The deceased was autopsied and the central nervous system was removed for a microscopic examination. The results showed microscopic lesions extending from the lumbar to the thoraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In oncology, prevention and management of errors are particularly critical because the patients' health status is poor and the drugs employed are toxic, have a low therapeutic index and are susceptible to be implicated in drug-drug interactions [13,14,15,16,17]. Most studies of medication errors in cancer care report high rates of severe events [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In oncology, prevention and management of errors are particularly critical because the patients' health status is poor and the drugs employed are toxic, have a low therapeutic index and are susceptible to be implicated in drug-drug interactions [13,14,15,16,17]. Most studies of medication errors in cancer care report high rates of severe events [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In an address Assault with the intention to commit grievous bodily harm and common assault to children (under 18 years) represent 9.7 and 11.8%, respectively, of all assaults [5]. Assaults with a sharp object in children are reported scarcely in the medical literature with mainly single case reports in the recent literature [6,7]. A report form the South African Medical Research Council in 2002 revealed that approximately 17% of school pupils carried weapons and that approximately 30% of school pupils had been involved in a physical assault in the past 6 months [8].…”
Section: Discussionmentioning
confidence: 98%
“…Misdiagnoses and treatment errors performed by hospital physicians are alarmingly common (Aronson 2008;Font Noguera, Climent, and Poveda Andrés 2008). Making matters even worse, some of them are fatal (Dettmeyer et al 2001;Tournel et al 2006). In order to improve patient safety in hospitals, a new design approach is needed (Grout 2007;Grout and Toussaint 2010).…”
mentioning
confidence: 98%